Quality assessment of Continuous Operating Reference Stations (CORS) - GPS stations in Mexico - Daniel Hernández-Andrade (Geodesy and Geodynamics, 2022)
The present analysis provided the quality assessment of 65 Continuous Operating Reference Stations (CORS) situated in and around Mexico using the data of about ten years (January 2010 to January 2020). To accomplish the assessment, we considered 4 quality indexes for performing the quality check, incluing the multipath effect on L1 and L2 bands, signal-to-noise ratio in both bands, cycle slips, and integrity. Meanwhile, a new reference parameter named regional values for Mexico (RVM) was calculated for the stations situated in Mexico. Additionally, an exhaustive analysis of the quality indicators in the worst and best cases was performed. The signal degradation was proved by a long-term time series and crustal deformation analysis in GAMIT/GLOBK platform. The results showed a strong correlation between integrity, cycle slips and daily observations time, and the multipath effect is strong in the case of outdated systems. The study indicates that the estimated quality indexes and values could be the basis for establishing new CORS in Mexico, and the errors corrections which cannot be mitigated in the post-processing stage would greatly help utilize the data for different scientific applications. The results were supported by deformation analysis in part of Baja California Peninsula in Mexico indicating northern and eastern velocity vector of −3.08 ± 0.02 mm/yr, −7.85 ± 0.02 mm/yr and −0.07 ± 0.03 mm/yr, −9.33 ± 0.02 mm/yr respectively at MPR1 and INEG stations.